2019
DOI: 10.1016/j.jns.2019.10.322
|View full text |Cite
|
Sign up to set email alerts
|

Intrathecal administration of AVXS-101 gene-replacement therapy (GRT) for spinal muscular atrophy type 2 (SMA2): Phase 1/2A study (strong)

Abstract: our model enables this for the investigation of new compounds in diseases involving demyelination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 0 publications
1
12
0
1
Order By: Relevance
“…At the time of analysis (March 8, 2019), seven patients were not hospitalized or receiving additional care, and three patients had started adjuvant nusinersen therapy (114). Interim results of an ongoing open-label phase 1-2 clinical trial of intrathecal administration of onasemnogene abeparvovec in patients with three SMN2 copies (STRONG, NCT03381729) showed a sustained gain of motor milestones and, as the primary outcome, treatment safety (52).…”
Section: Small Moleculesmentioning
confidence: 99%
“…At the time of analysis (March 8, 2019), seven patients were not hospitalized or receiving additional care, and three patients had started adjuvant nusinersen therapy (114). Interim results of an ongoing open-label phase 1-2 clinical trial of intrathecal administration of onasemnogene abeparvovec in patients with three SMN2 copies (STRONG, NCT03381729) showed a sustained gain of motor milestones and, as the primary outcome, treatment safety (52).…”
Section: Small Moleculesmentioning
confidence: 99%
“…Review of data 6–12 months after therapy showed no treated patients had lost motor milestones and some had gained milestones. 70 , 72 The trial was recently placed on a partial hold by the FDA recently given safety concerns from an animal model. 73 SPR1NT is an ongoing Phase III trial evaluating safety and efficacy of gene therapy administration to pre-symptomatic SMA patients with 2–3 copies of SMN2.…”
Section: Treatmentmentioning
confidence: 99%
“…Bardzo mało jest badań dotyczących zastosowania onasemnogene abeparvovec u pacjentów cierpiących na SMA2 i SMA3. Wyniki I fazy badania klinicznego o nazwie STRONG, które przedstawiane były na konferencjach naukowych w kwietniu i maju 2019 r. wykazały, że lek ten jest bardzo dobrze tolerowany i ma znaczący wpływ na poprawę stanu zdrowia u pacjentów chorych na SMA2 i SMA3 [27].…”
Section: Badania Kliniczneunclassified